1991
DOI: 10.1136/gut.32.12.1492
|View full text |Cite
|
Sign up to set email alerts
|

Controlled trial comparing two types of enteral nutrition in treatment of active Crohn's disease: elemental versus polymeric diet.

Abstract: To determine whether an

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
75
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(83 citation statements)
references
References 17 publications
4
75
0
2
Order By: Relevance
“…Rigaud 67 showed similar results with elemental and polymeric diets used as primary therapy for steroid-unresponsive CD. This fact suggests that some patients may benefit from NT after drug treatment failure 15 In a prospective study comparing TPN, oral diets plus TPN and elemental diets, Greenberg et al 31 observed no significant differences on remission, concluding that the benefits of these regimens were due to nutritional improvement.…”
Section: Enteral Nutrition (En)supporting
confidence: 57%
See 1 more Smart Citation
“…Rigaud 67 showed similar results with elemental and polymeric diets used as primary therapy for steroid-unresponsive CD. This fact suggests that some patients may benefit from NT after drug treatment failure 15 In a prospective study comparing TPN, oral diets plus TPN and elemental diets, Greenberg et al 31 observed no significant differences on remission, concluding that the benefits of these regimens were due to nutritional improvement.…”
Section: Enteral Nutrition (En)supporting
confidence: 57%
“…EN efficacy is also limited by disease location, once ileal disease has a faster and more complete response to treatment when compared to more diffuse disease or colonic or perianal disease 15,33 . Another limitation is the early relapse that occurs in 60 to 70% of patients in one year 67 . Despite the benefit of early remission induction on active CD, further data are necessary for better evaluation of enteral diet therapy on CD complicated by fistula and stenosis.…”
Section: Enteral Nutrition (En)mentioning
confidence: 99%
“…Both were already shown to be equally efficient as primary therapies for active CD. 21 Differences in nitrogen sources of enteral feeds are not relevant to their therapeutic efficacy, as elemental diets and polymeric diets are equally effective. 22 The results of this study were consistent with previous reports indicating that EN is efficacious for maintaining clinical remission of patients with CD and elemental diets and polymeric diets were equally effective.…”
Section: Discussionmentioning
confidence: 99%
“…Defined formula diets are usually more palatable and less expensive than are the elemental diets. While some investigators report no differences between elemental and defined formula diets in patients with acute CD [49,59,60] , Giaffer et al [61] found elemental diets to be more effective in active CD. A randomized double-blind trial in Crohn's patients demonstrated that elemental and polymeric (defined) diets, differing only in their source of nitrogen, were equally effective in reducing the Crohn's disease activity index (CDAI), and in inducing clinical remission [62] .…”
Section: Total Parenteral Nutrition (Tpn)mentioning
confidence: 99%